MOSLEM BROTHERHOOD, TRACK RECORD INDIAN MUSLIM SOLDIERS IN STRUGGLE OF INDONESIAN INDEPENDENCE (1945 -1950) - Sidqi, Kholfan Zubair; Kholiludin, Tedi; Widya Putri, Berlian Anis; Nafi'ah, Lailatun (TAWASUT, 2021)
MOSLEM BROTHERHOOD, TRACK RECORD INDIAN MUSLIM SOLDIERS IN STRUGGLE OF INDONESIAN INDEPENDENCE (1945 -1950) By Kholfan Zubair Taqo Sidqi Lecturer of FAI Unwahas Semarang Abstract Moslem brotherhood about Indian Muslim soldiers, especially at the beginning of the independence of the Republic of Indonesia, is very minimal for the audience of the current generation of Indonesia to know. Their track record (Indian Muslim Soldiers) can be achieved by collect fragments of writings from local fighters who interacted directly and fought against Dutch aggression. It started with a patrol of Indian Muslim soldiers finding the Qur'an in a resident's house. They also found a prayer room that had been burned. When faced with Indonesian fighters, they heard the screams of takbir blaring. Furthermore, there are several basic reasons ranging from fellow Muslims, fellow Asians, and fellow people who were colonized by Europeans, so the Indian Muslim soldiers as part of a unity British troops crossed over to the Indonesian fighters, fighting against the Dutch. Keywords: Moslem brotherhood, Indian Muslim Soldiers, and the struggle for Indonesian independence. Abstrak Persaudaraan muslim atau Ukhuwah Islamiyah prajurit muslim India terutama di awal kemerdekaan RI sangat minim sekali untuk d ketahui para khalayak generasi Indonesia sekarang. Jejak rekam mereka (Prajurit muslim India) dapat dicapai dengan mengumpulkan serpihan tulisan dari pejuang lokal yang berinteraksi langsung serta berjuang melawan agresi Belanda. Berawal dari patroli prajurit muslim India menemukan Al Qur’an di rumah penduduk. Mereka juga menemukan musholla yang telah dibakar. Saat berhadapan dengan pejuang Indonesia, mereka mendengar teriakan takbir yang membahana. Selanjutnya ada beberapa alasan mendasar mulai dari sesama orang Islam, sesama orang asia, serta sesama orang yang dijajah bangsa Eropa, maka para prajurit muslim India sebagai bagian kesatuan tempur pasukan Inggris menyeberang ke pihak pejuang Indonesia, berjuang bertempur melawan Belanda. Kata kunci: Ukhuwah Islamiyah, Prajurit Muslim India, dan perjuangan kemerdekaan Indonesia.